The dipeptidyl peptidase‐4 (DPP‐4) inhibitor teneligliptin enhances brown adipose tissue function, thereby preventing obesity in mice. Issue 11 (19th September 2018) - Takeda, Kenichiro; Sawazaki, Honami; Takahashi, Haruya; Yeh, Yu‐Sheng; Jheng, Huei‐Fen; Nomura, Wataru; Ara, Takeshi; Takahashi, Nobuyuki; Seno, Shigeto; Osato, Naoki; Matsuda, Hideo; Kawada, Teruo; et al.
Abstract : To clarify the effects of a dipeptidyl peptidase‐4 (DPP‐4) inhibitor on whole‐body energy metabolism, we treated mice fed a high‐fat diet (HFD) with teneligliptin, a clinically available DPP‐4 inhibitor. Teneligliptin significantly prevented HFD‐induced obesity and obesity‐associated metabolic disorders. It also increased oxygen consumption rate and upregulated uncoupling protein 1 (UCP1) expression in both brown adipose tissue (BAT) and inguinal white adipose tissue (iWAT), suggesting that it enhances BAT function. Soluble DPP‐4 inhibited β‐adrenoreceptor‐stimulated UCP1 expression in primary adipocytes, and this inhibition was prevented in the presence of teneligliptin, or an extracellular signal‐related kinase inhibitor. These results indicate that soluble DPP‐4 inhibits β‐adrenoreceptor‐stimulated UCP1 induction and that chronic DPP‐4 inhibitor treatment may prevent obesity through the activation of BAT function. Abstract : Proposed schema of the preventive effect of teneligliptin on obesity in adipocytes. sDPP‐4‐mediated ERK activation, acting through PAR2, suppresses β‐adrenoreceptor‐stimulated UCP1 upregulation in adipocytes. Teneligliptin treatment can prevent this suppression, suggesting that this mechanism might be related to teneligliptin‐induced activation of BAT function in vivo . Teneligliptin‐activated BAT function enhances energy expenditure, thereby preventing obesity.